Neodiplopeltula gen. nov. from the west coast of Sweden and reappraisal of the genus Diplopeltula Gerlach, 1950 (Nematoda, Diplopeltidae) - Holovachov, Oleksandr; Boström, Sven (European Journal of Taxonomy, 2018)
The new genus Neodiplopeltula gen. nov. is proposed to accommodate those species from the genus Diplopeltula Gerlach, 1950 that possess the following morphological characters: amphids in the shape of an elongated loop, a well-developed subcylindrical stoma and outstretched ovaries. The genus Diplopeltula is considered genus inquirendum et incertae sedis. Four species placed in Neodiplopeltula gen. nov. are redescribed. The following taxonomic changes are proposed: Neodiplopeltula asymmetrica (Allgén, 1935) gen. et comb. nov.; Neodiplopeltula barentsi (Steiner, 1916) gen. et comb. nov.; Neodiplopeltula bathmanni (Jensen, 1991) gen. et comb. nov.; Neodiplopeltula cuspidiboja (Leduc, 2017) gen. et comb. nov.; Neodiplopeltula indica (Gerlach, 1962) gen. et comb. nov.; Neodiplopeltula intermedia (Gerlach, 1954) gen. et comb. nov.; Neodiplopeltula obesa (Nguyen Vu Thahn, Nguyen Thahn Hien & Gagarin, 2012) gen. et comb. nov.; Neodiplopeltula onusta (Wieser, 1956) gen. et comb. nov.; Neodiplopeltula ovalis (Ditlevsen, 1928) gen. et comb. nov. and Neodiplopeltula tchesunovi (Fadeeva & Mordukhovich, 2013) gen. et comb. nov. New synonyms include: Diplopeltis asymmetricus Allgén, 1935 and Diplopeltis ovalis Ditlevsen, 1928 are synonimised with Neodiplopeltula barentsi (Steiner, 1916) gen. et comb. nov.; Diplopeltula tchesunovi Fadeeva & Mordukhovich, 2013 is synonimised with Neodiplopeltula onusta (Wieser, 1956) gen. et comb. nov.; the male of Diplopeltula cuspidiboja Leduc, 2017 is synonimised with Neodiplopeltula barentsi gen. et comb. nov. and the female with N. bathmanni gen. et comb. nov. A key to the species of Neodiplopeltula gen. nov. is provided.